The Pengaruh Aplikasi Photosynthetic Bacteria Terhadap Klorofil Daun dan Produksi Kacang Merah Varietas Inerie - Yosefina Lewar; Ali Hasan; Stormy Vertygo; Maria Klara Salli; Maria S. Medho; Dina V. Sinlae (Politeknik Negeri Lampung., 2025)
Kidney beans (Phaseolus vulgaris), belonging to the Leguminosae family and classified as C3 plants, typically exhibit slower photosynthesis and lower biomass production under high light intensity and hot temperatures. To overcome these limitations and enhance photosynthetic efficiency, external stimulation of plant physiological processes is crucial. One promising approach involves the application of Photosynthetic Bacteria (PSB), known for their independent photosynthetic capabilities. This study aimed to evaluate the impact of PSB application at various growth stages on leaf chlorophyll content and the yield of 'Inerie' variety kidney beans, and to identify the optimal application timing. A Randomized Block Design (RBD) was employed, comparing seven PSB application treatments: a control, single applications at the exponential growth, flower initiation, and pod formation stages, and combined applications (exponential + flower initiation; exponential + pod formation; flower initiation + pod formation; and exponential + flower initiation + pod formation). The results indicated that PSB application at different growth stages significantly influenced both chlorophyll content and kidney bean production. The optimal application time was identified as the flower initiation phase, which significantly increased chlorophyll a content to 8.51 mg/g, total chlorophyll to 14.69 mg/g, and enhanced yield components, resulting in 22.22 pods per plant, 63.06 seeds per plant, and a seed weight of 24.44 g.